2016
DOI: 10.3109/10826084.2015.1110170
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Psychostimulant Use Among Young Adults: A Narrative Review of Qualitative Studies

Abstract: Prescription psychostimulant use among young adults is anchored in contemporary normativity and cannot be separated from the developing performance ethic within North-American and other Western societies. We suggest that pharmaceuticalization and Actor-Network Theory are useful conceptual tools to frame future research efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…When they exclude medical users of ADHD medications as enhancemental users of ADHD medications, researchers are policing the boundary between medicine and enhancement. (p. 7)Whether for therapy or enhancement, the use of these drugs creates relations between pharmacological “objects” and their consumers (Greene & Sismondo, 2015; Hardon & Sanabria, 2017) embedded in contemporary values around achievement and normalcy (Robitaille & Collins, 2016; N. Rose, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…When they exclude medical users of ADHD medications as enhancemental users of ADHD medications, researchers are policing the boundary between medicine and enhancement. (p. 7)Whether for therapy or enhancement, the use of these drugs creates relations between pharmacological “objects” and their consumers (Greene & Sismondo, 2015; Hardon & Sanabria, 2017) embedded in contemporary values around achievement and normalcy (Robitaille & Collins, 2016; N. Rose, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Others find no effects of strain on illicit prescription drug use (Maahs, Weidner, & Smith, 2016). A review of qualitative studies suggests that the nonmedical use of psychostimulants is seen as a tool to navigate stress, to maintain a socially acceptable standing within one's reference group, and to adhere to the performance ethic in North American and other Western societies (Robitaille & Collin, 2016). For example, studies found that CE-drugs are seen as a quick fix and a resource for coping with high demands (Forlini & Racine, 2009;Partridge, Bell, Lucke, & Hall, 2012).…”
mentioning
confidence: 99%
“…The present decision-making model needs to be considered in light of these interviewees describing their current or previous ADHD medicine intake to be consistent and not situation-based, i.e., not used to, e.g., maximise concentration for exams, such as reported by Fleishmann and Kalinski [ 33 ]. The factors performance and ambitions are essentially different from the non-medical use of prescription stimulants for non-medical matters as has previously been reported to occur in this age group (see, e.g., Robitaille and Collin [ 34 ]).…”
Section: Discussionmentioning
confidence: 81%